Carbon fiber filament, graphene and polymer compounded gas diffusion layer as well as preparation method and application thereof

Through the preparation method of gas diffusion layer composited by carbon fiber filaments and graphene and polymers, the problem of poor mechanical strength and conductivity of gas diffusion layer for fuel cells is solved, and high mechanical strength and conductivity are improved, which is suitable for fuel cells. gas diffusion layer application.

CN119297306APending Publication Date: 2025-01-10ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411660515.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing gas diffusion layer for fuel cells has problems such as poor mechanical strength and conductivity and low thermal diffusion coefficient.

Method used

The gas diffusion layer preparation method is adopted to combine carbon fiber filaments with graphene and polymer composites. By unfolding carbon fiber filaments, alternating winding of vertical and horizontal lateral, combining graphene slurry and polymer materials, thermal rolling and high-temperature carbonization are carried out to form the base layer and microstructure Pore ​​layer to improve mechanical properties and electrical conductivity.

Benefits of technology

It has achieved the improvement of high mechanical strength, conductivity and thermal conductivity, meets the strict requirements of the gas diffusion layer of fuel cell, and has a simple process and controllable quality, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297306A_ABST
    Figure CN119297306A_ABST
Patent Text Reader

Abstract

The invention provides a carbon fiber filament, graphene and polymer compounded gas diffusion layer as well as a preparation method and application thereof, and relates to the technical field of hydrogen energy and fuel cells. The preparation method of the gas diffusion layer comprises the following steps: spreading a carbon fiber bundle to obtain carbon fibers, and then winding the carbon fibers on a substrate longitudinally and transversely alternately to obtain a carbon fiber layer preform; mixing graphene with a high polymer material to form a substrate layer graphene slurry; mixing carbon black, graphene powder, a hydrophobic binder and a solvent to obtain microporous layer slurry; coating the two sides of the carbon fiber layer preform with the substrate layer graphene slurry, performing hot rolling or hot pressure maintaining after drying, and performing high-temperature carbonization in inert gas to obtain a substrate layer; the surface of one side of the substrate layer is coated with the microporous layer slurry, the gas diffusion layer is obtained through drying, the gas diffusion layer has the good mechanical property, low resistivity, high porosity and good hydrophobicity, the preparation process is simple, the quality is controllable, and batch production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen energy and fuel cells, and in particular to a gas diffusion layer composited with carbon fiber filaments, graphene and polymers, and a preparation method and application thereof. Background Art

[0002] With the increasing concern about the environment and energy crisis, the development of clean and sustainable energy is imperative. As a new generation of energy storage and conversion devices, fuel cells have attracted much attention due to their high energy conversion efficiency, continuous operability and other advantages. Fuel cells use fuel and oxygen (or air) to directly release electrical energy through electrochemical reactions. Unlike secondary batteries that need to be charged, fuel cells can continue to generate electricity as long as there is a supply of fuel and oxygen. This is superior to the intermittent behavior of other renewable energy sources such as solar and wind energy. In addition, due to the lack of heat exchange and mechanical transmission processes, the efficiency of fuel cells is much higher than other power generation systems. The fuels used by fuel cells are mainly clean energy such as hydrogen, methane, methanol, and ethanol. There is no combustion during the entire working process, so its energy conversion efficiency is not limited by the Carnot cycle, resulting in a high specific energy. It has very good application prospects. Such as can be used as a power system for vehicles, a mobile small power supply system, an emergency power supply for public facilities, etc.

[0003] The core membrane electrode (MEA) of the fuel cell is composed of the anode gas diffusion layer (GDL), the anode catalyst layer (CL), the electrolyte layer, the cathode CL and the cathode GDL stacked in sequence. The GDL provides a way for gas diffusion and drainage as well as electrical connection between the CL and the bipolar plate (BP), and also provides mechanical support for the MEA. Such as supporting the catalyst layer, collecting current, providing multiple transmission channels such as mass, protons, and electrons, etc. Therefore, the GDL is required to have many high-standard characteristics such as high conductivity, high stability, high water management ability, high air permeability, and corrosion resistance.

[0004] The gas diffusion layer is usually composed of a base layer and a microporous layer. The base layer is mainly composed of carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper. Foam metal and metal mesh are also used to prepare the base layer. As fuel cells develop towards lightweight, miniaturized and low-cost directions, carbon materials with superior performance have gradually replaced the base layer of metal mesh materials and become the preferred material for preparing the base layer. The carbon fiber paper base layer can meet the high standard requirements of the gas diffusion layer, and its porous structure provides a transmission channel for the reactant gas and the product water. The microporous layer is usually composed of carbon black and a hydrophobic binder (such as polyvinylidene fluoride, polytetrafluoroethylene, etc.), which affects the pore size distribution, gas and water permeability, conductivity, etc. of the gas diffusion layer.

[0005] The base layer of the traditional gas diffusion layer is usually composed of 6-8 mm long carbon fibers and is generally between 150 and 250 mm thick. The traditional method for preparing the base layer of the gas diffusion layer is to use conventional wet papermaking technology, that is, a certain amount of chopped carbon fibers and a fixed amount of wood pulp are placed in a fiber disintegrator, a fiber slurry dispersant solution is added, stirred to fully mix, and the carbon paper is made into sheets and dried on a paper sample copying machine to obtain a carbon paper base paper. The carbon paper obtained by the traditional preparation process has a small carbon fiber length and is difficult to disperse evenly in the pulp, which easily leads to uneven thickness of the carbon paper, poor mechanical strength and conductivity. In order to solve the above problems, those skilled in the art are in urgent need of developing a gas diffusion layer for fuel cells with good conductivity, high thermal diffusion coefficient, large specific surface area and strong chemical inertness. Summary of the invention

[0006] The purpose of the present invention is to provide a gas diffusion layer composited with carbon fiber filaments, graphene and polymers, and a preparation method and application thereof, so as to solve the problems of poor mechanical strength and electrical conductivity and low thermal diffusion coefficient of the existing gas diffusion layer for fuel cells.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer, comprising the following steps:

[0009] 1) Spreading the carbon fiber bundle to obtain spread carbon fiber filaments, and then winding the spread carbon fiber filaments alternately vertically and horizontally on a base material with a smooth surface to obtain a carbon fiber layer preform;

[0010] Mixing graphene slurry with polymer material to prepare base layer graphene slurry;

[0011] Dispersing carbon black, graphene slurry and hydrophobic binder in a solvent to obtain a microporous layer slurry;

[0012] 2) coating the base layer graphene slurry on both sides of the carbon fiber layer preform, drying, hot rolling or hot holding, and then high-temperature carbonizing in an inert gas to obtain the base layer;

[0013] 3) coating the microporous layer slurry on one side of the substrate layer, and drying the slurry to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0014] Preferably, the width of the unfolded carbon fiber filaments in step 1) is 40 to 70 cm;

[0015] The length of the base material is 0.3 to 0.8 m, and the width of the base material is 0.3 to 0.8 m;

[0016] The number of winding layers is 6 to 10 layers.

[0017] Preferably, the mass ratio of the graphene slurry to the polymer material in step 1) is 1 to 120:1;

[0018] The solid content of the graphene slurry is 13.5-17.5%;

[0019] The number of atomic layers of graphene in the graphene slurry is less than 10, and the length and width of a single microsheet of graphene are independently between 2 and 7 mm.

[0020] Preferably, the polymer material in step 1) includes one or more of waterborne polyurethane, epoxy resin AB glue, water-soluble phenolic resin, polyacrylic acid and polyvinyl alcohol;

[0021] The solid content of the polymer material is ≥60%.

[0022] Preferably, the mass ratio of carbon black, graphene powder, hydrophobic binder and solvent in step 1) is 8:8:1-8:160-200;

[0023] The carbon black has a particle size of 30 to 50 nm and a specific surface area of ​​200 to 1400 m 2 / g;

[0024] The hydrophobic binder is polytetrafluoroethylene and / or polyvinylidene fluoride, and the viscosity of the hydrophobic binder is 0.2 to 20 Pa·S;

[0025] The solvent includes one or more of N-methylpyrrolidone, ethanol and water.

[0026] Preferably, in step 2), the mass ratio of the total coating amount of the base layer graphene slurry to the carbon fiber layer preform is 2 to 5:1;

[0027] The drying temperature is 80-120°C and the drying time is 4-8h;

[0028] The temperature of the hot roller pressing is 70-90°C, the roller pressing interval is 0.06-0.12mm, and the number of hot roller pressing is 2-5 times;

[0029] The temperature of the heat-pressing is 250-270° C., the pressure of the heat-pressing is 220-420 KPa, and the time of the heat-pressing is 20-30 minutes.

[0030] Preferably, the high temperature carbonization in step 2) is carried out at a temperature of 1000-1200° C., for a time of 30-60 min, and at a heating rate of 5-15° C. / min.

[0031] Preferably, the coating amount of the microporous layer slurry on the surface of the substrate in step 3) is 1-8 mg / cm 2 ;

[0032] The drying temperature is 300-400° C. and the drying time is 30-60 minutes.

[0033] The present invention also provides a gas diffusion layer composited with carbon fiber filaments, graphene and polymers prepared by the above preparation method, comprising a base layer and a microporous layer;

[0034] The thickness of the base layer is 0 to 130 μm, the thickness of the base layer is not 0, and the bending strength is ≥ 10 MPa;

[0035] The thickness of the microporous layer is 10-40 μm.

[0036] The present invention also provides an application of the above-mentioned carbon fiber filaments, graphene and polymer composite gas diffusion layer in a fuel cell.

[0037] The present invention has at least the following beneficial effects:

[0038] The present invention abandons the traditional idea. Compared with the traditional preparation process of millimeter-scale short-cut carbon fiber wet papermaking technology, on the one hand, it uses uncut carbon fiber and graphene for compounding, so that the composite material maintains the high tensile strength and bending strength of the carbon fiber original filament to a certain extent. On the other hand, through the polymerization reaction between the polymer materials, it is closely combined with the carbon fiber and the molecular distance is reduced, so that the carbonized composite material has higher mechanical properties.

[0039] The present invention uses uncut carbon fibers to improve the electronic conductivity. On the other hand, by adding graphene and polymer, each cross-sectional carbon fiber unit is stabilized to fix the carbon fiber. First, graphene is a sp 2 Hybridized carbon atoms are tightly packed into a single-layer two-dimensional honeycomb lattice structure. Each carbon atom on the graphene sheet has an unbonded p-orbital electron, which interacts with the p-orbital electron cloud to form a conjugated large π bond. Secondly, the energy factor of the graphene lattice vibration is mainly phonon, so it has excellent thermal conductivity. The in-plane thermal conductivity at room temperature is as high as 5300W / (m·K). In addition, graphene also has a low density (<2.2g / cm 3), small thermal expansion coefficient, high thermal emissivity, good high temperature stability (temperature resistance can reach about 3000℃ in oxygen-free environment), strong particle impact resistance and other advantages. Therefore, graphene is an ideal high-performance thermal management material suitable for extreme environments. When graphene layers are stacked, the electrons in the layers can also provide good conductivity. Its π electrons are highly delocalized within the layer and can move freely, so it has very good conductivity. Because of its special structural characteristics, and after carbonization and graphitization treatment, most of the polymer materials are eliminated, further reducing the resistivity and increasing the thermal diffusion coefficient in the composite material.

[0040] The carbon fiber filaments, graphene and polymer composite gas diffusion layer obtained by the present invention has good mechanical properties, high porosity, large mechanical strength, strong hydrophobicity and high conductivity, and the preparation process is simple, the quality is controllable, and it can be mass-produced. In addition, the area of ​​the diffusion layer can reach 40×40cm~70×70cm, which is large and can be used in fuel cell vehicles as a whole. The carbon fiber filaments, graphene and polymer composite gas diffusion layer prepared by the present invention is expected to meet the stringent requirements of the fuel cell gas diffusion layer with its superior performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a scanning electron microscope (SEM) image of the gas diffusion layer prepared in Example 3. Figure 1 a in the figure is a SEM plan view of the gas diffusion layer substrate layer prepared in step (4) of Example 3 before carbonization; Figure 1 b is a SEM cross-sectional view of the gas diffusion layer substrate after carbonization in Example 3; Figure 1 c and Figure 1 d in the figure is a SEM plane image of the gas diffusion layer composited with carbon fiber filaments, graphene and polymer in Example 3 at different magnifications; Figure 1 e in which is a SEM cross-sectional view of the gas diffusion layer substrate in Example 3;

[0042] Figure 2 This is the contact angle diagram of the gas diffusion layer prepared in Example 3. Figure 2 a in the figure is the contact angle diagram of the gas diffusion layer substrate prepared in step (4) of Example 3, Figure 2 b is the contact angle diagram of the carbon fiber filaments and the gas diffusion layer composited with graphene and polymer obtained after adding a microporous layer on the surface;

[0043] Figure 3 This is a graph showing the tensile strength test results of the base layer prepared in step (4) of Example 9 before and after carbonization. Figure 3 The a line in the figure is the tensile strength of the substrate before carbonization. Figure 3 The b line in the figure is the tensile strength of the base layer after carbonization;

[0044] Figure 4 This is a pore size distribution diagram of the base layer in the gas diffusion layer composited with carbon fiber filaments, graphene and polymer prepared in Example 3 and Example 8. DETAILED DESCRIPTION

[0045] The present invention provides a method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer, comprising the following steps:

[0046] 1) Spreading the carbon fiber bundle to obtain spread carbon fiber filaments, and then winding the spread carbon fiber filaments alternately vertically and horizontally on a base material with a smooth surface to obtain a carbon fiber layer preform;

[0047] Mixing graphene slurry with polymer material to prepare base layer graphene slurry;

[0048] Dispersing carbon black, graphene slurry and hydrophobic binder in a solvent to obtain a microporous layer slurry;

[0049] Dispersing carbon black, graphene powder and a hydrophobic binder in a solvent to obtain a microporous layer slurry;

[0050] 2) coating the base layer graphene slurry on both sides of the carbon fiber layer preform, drying, hot rolling or hot holding, and then high-temperature carbonizing in an inert gas to obtain the base layer;

[0051] 3) coating the microporous layer slurry on one side of the substrate layer, and drying the slurry to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0052] In the present invention, the method of spreading the carbon fiber bundle is as follows: placing the carbon fiber roll at one end of the water tank, flush with the height of the water tank, guiding the carbon fiber bundle from the carbon fiber roll into the water tank filled with ultrapure water by means of a guide roller, pulling the carbon fiber bundle to the other end of the water tank and keeping the carbon fiber bundle from flipping, immersing the carbon fiber bundle in ultrapure water for spreading, and longitudinal pulling and lateral spreading are carried out simultaneously until the carbon fiber filaments reach the target width; the carbon fiber layer preform is used as a supporting layer and the carbon fiber wet spreading method is adopted to make the carbon fiber filaments spread evenly, providing conditions for the uniform thickness of the composite material.

[0053] In the present invention, the carbon fiber spreading water tank and the base material with a smooth surface described in step 1) are preferably made of tempered glass.

[0054] The model of the carbon fiber roll is T700SC-12000-50C, the diameter of the carbon fiber filament is 7 μm, the tensile strength is ≥4900 MPa, the modulus is ≥230 GPa, the linear density is 760±20 g / km, the elongation is 1.5±0.02%, and the density is 1.8±0.02 g / cm3 , carbon content ≥95%, resistance 33Ω / m;

[0055] The length, width and depth of the water tank are 1.8-5m, 0.6-1m and 0.015-0.05m, respectively, preferably 2.5-4.5m, 0.7-0.9m and 0.02-0.04m, and more preferably 3-4m, 0.8-9m and 0.025-0.03m.

[0056] In the present invention, the width of the unfolded carbon fiber filaments in step 1) is 40 to 70 cm, preferably 45 to 65 cm, more preferably 50 to 60 cm, and more preferably 55 cm.

[0057] In the present invention, the length of the base material is 0.3 to 0.8 m, preferably 0.4 to 0.7 m, and more preferably 0.5 to 0.6 m. The width of the base material is 0.3 to 0.8 m, preferably 0.4 to 0.7 m, and more preferably 0.5 to 0.6 m. The width of the base material should be greater than or equal to the width of the unfolded carbon fiber filaments.

[0058] In the present invention, the number of layers of the winding is 6 to 10, which can be 6, 7, 8, 9 or 10 layers; the winding method is alternating vertically and horizontally.

[0059] The carbon fiber layer preform (without cutting carbon fiber) is obtained by directly winding the unfolded carbon fiber filaments. On the one hand, it is beneficial to electron conduction and enhances the conductivity of the composite material; on the other hand, compared with chopped carbon fiber, the use of uncut carbon fiber also ensures mechanical strength. Graphene increases the thermal conductivity of the composite material and has a positive effect on the fixation of carbon fiber filaments. After high-temperature sintering, the addition of graphene powder to the microporous layer maintains a good load and efficient utilization of the catalyst layer. The carbon fibers are evenly spread and orderly crisscrossed and anchored by graphene sheets, which is conducive to the uniform arrangement and effective conduction of gas.

[0060] In the present invention, the mass ratio of the graphene slurry to the polymer material in step 1) is 1 to 120:1, preferably 5 to 100:1, more preferably 10 to 80:1, further preferably 15 to 50:1, and more preferably 5 to 30:1.

[0061] In the present invention, the solid content of the graphene slurry is 13.5-17.5%, preferably 14-17%, more preferably 14.5-16.5%, and more preferably 15-16%.

[0062] In the present invention, the graphene slurry described in step 1) is obtained by mechanical exfoliation with a nano sand mill, and the number of atomic layers of graphene in the graphene slurry is less than 10, preferably 2 to 8, more preferably 3 to 7, and more preferably 4 to 6; the length and width of a single microsheet of graphene in the graphene slurry are independently between 2 and 7 mm, preferably 3 to 6 mm, and more preferably 4 to 5 mm.

[0063] In the present invention, the polymer material includes one or more of waterborne polyurethane, epoxy resin AB glue, water-soluble phenolic resin, polyacrylic acid and polyvinyl alcohol, and the solid content of the polymer material is ≥60%, preferably 60-80%, more preferably 65-75%, and more preferably 70%.

[0064] In the present invention, the mass ratio of carbon black, graphene powder, hydrophobic binder and solvent in step 1) is 8:8:1-8:160-200, preferably 8:8:2-7:165-195, further preferably 8:8:3-6:170-190, and more preferably 8:8:4-5:175-185.

[0065] In the present invention, the particle size of the carbon black is 30 to 50 nm, preferably 32 to 48 nm, more preferably 35 to 45 nm, and more preferably 38 to 42 nm; the specific surface area is 200 to 1400 m 2 / g, preferably 500 to 1200 m 2 / g, more preferably 700 to 1000 m 2 / g, more preferably 800 to 900 m 2 / g.

[0066] In the present invention, the hydrophobic binder is polytetrafluoroethylene and / or polyvinylidene fluoride, and the viscosity of the hydrophobic binder is 0.2 to 20 Pa·S, preferably 3 to 18 Pa·S, more preferably 5 to 15 Pa·S, and even more preferably 8 to 12 Pa·S.

[0067] In the present invention, the solvent is one or more of N-methylpyrrolidone, ethanol and water.

[0068] In the present invention, the preparation method of the graphene powder is: mixing artificial graphite powder with deionized water or mixing artificial graphite powder, sodium carboxymethyl cellulose (CMC) and deionized water and mechanically exfoliating with a nano sand mill, and then freeze-drying and ball milling to obtain graphene powder; the number of layers of the graphene powder is 3 to 5 layers, and the particle size of the graphene powder is 50 μm.

[0069] In the present invention, the carbon black is one of AB CB11 acetylene black, KB EC-600JD, Cabot Vulcan XC-72R, and Carbonblack acetylene.

[0070] In the present invention, the mass ratio of the total coating amount of the base layer graphene slurry to the carbon fiber layer preform in step 2) is 2 to 5:1, preferably 2.5 to 4.5:1, more preferably 3 to 4:1, and more preferably 3.5 to 3.8:1.

[0071] In the present invention, the drying temperature is 80-120°C, preferably 85-115°C, more preferably 90-110°C, and more preferably 95-100°C; the drying time is 4-8h, preferably 4.5-7.5h, more preferably 5-7h, and more preferably 5.5-6.5h.

[0072] In the present invention, the temperature of the hot rolling is 70-90°C, preferably 75-85°C, further preferably 78-83°C, and more preferably 80°C; the rolling spacing is 0.2-0.3mm, preferably 0.22-0.28mm, further preferably 0.24-0.26mm, and more preferably 0.25mm; the number of hot rolling is 3-5 times, which can be selected as 3 times, 4 times or 5 times; the hot rolling method is adopted to make the gas diffusion layer composite of carbon fiber filaments, graphene and polymers uniform in thickness and smooth in surface.

[0073] In the present invention, the temperature of the hot pressing is 250-270°C, preferably 253-268°C, further preferably 255-265°C, and more preferably 258-260°C; the pressure of the hot pressing is 220-420KPa, preferably 250-400KPa, further preferably 280-380KPa, and more preferably 300-350KPa; the time of the hot pressing is 20-30min, preferably 22-28min, further preferably 24-26min, and more preferably 25min.

[0074] In the present invention, the temperature of the high-temperature carbonization is 1000-1200°C, preferably 1050-1150°C, more preferably 1080-1120°C, and more preferably 1100°C; the time is 30-60min, preferably 35-55min, more preferably 40-50min, and more preferably 45min; the heating rate is 5-15°C / min, preferably 7-13°C / min, and more preferably 9-11°C / min.

[0075] In the present invention, the high temperature carbonization atmosphere is one of nitrogen and argon.

[0076] In the present invention, the coating amount of the microporous layer slurry in step 3) on the surface of the base layer is 1-8 mg / cm 2 , preferably 3 to 7.5 mg / cm 2 , more preferably 4 to 7 mg / cm 2 , more preferably 5 to 6 mg / cm 2 .

[0077] In the present invention, the drying temperature is 300-400°C, preferably 320-380°C, more preferably 330-360°C, more preferably 340-350°C; the drying time is 30-60min, preferably 35-55min, more preferably 40-50min, more preferably 42-48min.

[0078] The present invention also provides a gas diffusion layer composited with carbon fiber filaments, graphene and polymers prepared by the above preparation method, comprising a base layer and a microporous layer.

[0079] In the present invention, the thickness of the base layer is 0 to 130 μm, preferably 20 to 110 μm, more preferably 40 to 90 μm, and more preferably 50 to 80 μm. The thickness of the base layer is not 0; and the flexural strength is ≥ 10 MPa.

[0080] In the present invention, the thickness of the microporous layer is 10 to 40 μm, preferably 15 to 35 μm, more preferably 20 to 30 μm, and even more preferably 22 to 28 μm.

[0081] The present invention also provides an application of the above-mentioned carbon fiber filaments, graphene and polymer composite gas diffusion layer in a fuel cell.

[0082] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0083] Example 1

[0084] (1) Carbon fiber filaments on glass substrate:

[0085] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0086] (2) Preparation of carbon fiber layer preform:

[0087] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0088] (3) Preparation of graphene slurry for the base layer:

[0089] 3.88 g of waterborne polyurethane (solid content 60%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred. Then, 3.88 g of epoxy resin A glue and 1.94 g of epoxy resin B glue (Fossil) were added in sequence, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0090] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0091] The base layer graphene slurry is sprayed on one side of the carbon fiber layer preform with a spray gun, and the spraying amount is 0.013g / cm 2 , and then put the composite material into a common oven and dry it at 120℃ for 6h. Cut the composite material from the side of the glass plate and transfer it to a roller press. The roller pressing temperature is 80℃, the roller pressing interval is 100μm, and the roller pressing is repeated twice. The base layer graphene slurry is sprayed on the other side of the composite material, and the spraying amount is 0.013g / cm 2 , drying, repeating the above rolling operation twice, drying. Then put it into a high temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, the gas atmosphere is nitrogen. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​40cm×40cm.

[0092] (5) Preparation of microporous graphene slurry:

[0093] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 600mg of the above heat-treated graphene powder, 600mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 600mg of polyvinylidene fluoride (mass ratio of 1:1:1), mix the three evenly, and grind them in a mortar for 30min. Then disperse them in 16g of N-methylpyrrolidone by ultrasonication to form a viscous and flowable microporous layer slurry.

[0094] (6) Composite of base layer and microporous layer:

[0095] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0096] Example 2

[0097] (1) Carbon fiber filaments on glass substrate:

[0098] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0099] (2) Preparation of carbon fiber layer preform:

[0100] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0101] (3) Preparation of graphene slurry for the base layer:

[0102] 7.76 g of water-soluble phenolic resin (solid content 70%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0103] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0104] The base layer graphene slurry is coated on one side of the carbon fiber layer preform, and the coating amount is 0.013g / cm 2, and then put it into a common oven and dry it at 120℃ for 6h. The composite material was completely peeled off from the glass plate and then transferred to a roller press. The rolling temperature was 80℃ and the rolling spacing was 100μm. The rolling was repeated twice. The base layer graphene slurry was coated on the other side of the composite material with a coating amount of 0.013g / cm 2 , drying, repeat the above rolling operation twice. Then put it into a high temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, the gas atmosphere is nitrogen. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​40cm×40cm and a thickness of 0.103mm. After testing, the conductivity of the substrate after high temperature carbonization is 17.81S / mm, and the conductivity is greatly improved.

[0105] (5) Preparation of microporous graphene slurry:

[0106] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 600mg of the above heat-treated graphene powder, 600mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 600mg of polyvinylidene fluoride (mass ratio of 1:1:1), mix the three evenly, and grind them in a mortar for 30min. Then disperse them in 16g of N-methylpyrrolidone by ultrasonication to form a viscous and flowable microporous layer slurry.

[0107] (6) Composite of base layer and microporous layer:

[0108] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0109] Example 3

[0110] (1) Carbon fiber filaments on glass substrate:

[0111] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0112] (2) Preparation of carbon fiber layer preform:

[0113] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0114] (3) Preparation of graphene slurry for the base layer:

[0115] 3.88 g of waterborne polyurethane (solid content 60%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0116] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0117] The base layer graphene slurry is sprayed on one side of the carbon fiber layer preform with a spray gun, and the coating amount is 0.013g / cm 2 The composite material was then placed in a common oven and dried at 120°C for 6 hours. The composite material was completely removed from the glass plate, and the base layer graphene slurry was sprayed on the other side of the composite material with a coating amount of 0.013 g / cm 2 , dried. Then the composite material is placed on a flat hot press for hot pressing, the hot pressing temperature is set to 270°C, the pressure is 320KPa, and the holding time is 20min. Then it is placed in a high-temperature furnace and heated to 1000°C at a rate of 5°C / min, and then carbonized for 30min, and the gas atmosphere is nitrogen. Naturally cool to room temperature and take out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate), with an area of ​​40cm×40cm, a thickness of 0.123mm, and a conductivity of 13.73S / mm.

[0118] (5) Preparation of microporous graphene slurry:

[0119] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 600mg of the above heat-treated graphene powder, 600mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 400mg of polyvinylidene fluoride (mass ratio of 2:2:1), mix the three evenly, and grind them in a mortar for 30min. Then ultrasonically disperse them in 16g of N-methylpyrrolidone to form a viscous and flowable microporous layer slurry.

[0120] (6) Composite of base layer and microporous layer:

[0121] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0122] Figure 1 This is a scanning electron microscope (SEM) image of the gas diffusion layer prepared in this embodiment. Figure 1 a in which is a SEM plan view of the gas diffusion layer substrate layer prepared in step (4) before carbonization;

[0123] Figure 1 b is the SEM cross-sectional image of the gas diffusion layer substrate after carbonization; Figure 1 c and Figure 1 Figure d in the figure is the SEM plane image of the gas diffusion layer composited with carbon fiber filaments, graphene and polymer at different magnifications. It can be seen from the figure that the carbon nanoparticles are evenly covered on the substrate layer; Figure 1 Figure e is a SEM cross-sectional view of the gas diffusion layer substrate, from which it can be seen that the carbon fiber filaments are evenly spread.

[0124] Figure 2 is the contact angle diagram of the gas diffusion layer prepared in this embodiment, Figure 2 a in the figure is the contact angle diagram of the gas diffusion layer substrate prepared in step (4), and the contact angle is 91°; Figure 2 Figure b is a contact angle diagram of the gas diffusion layer of carbon fiber filaments, graphene and polymer composite obtained after adding a microporous layer on the surface, and the contact angle is 140°; the liquid in the above contact angle diagram is water, and it can be seen from the figure that the microporous layer improves the hydrophobicity of the gas diffusion layer.

[0125] Example 4

[0126] (1) Carbon fiber filaments on glass substrate:

[0127] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 8m, 1.1m, 0.05m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank, and is flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 70cm is obtained.

[0128] (2) Preparation of carbon fiber layer preform:

[0129] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.7 m and 0.7 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0130] (3) Preparation of graphene slurry for the base layer:

[0131] 38.8 g of waterborne polyurethane (solid content 60%, McLean) was added to 400 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0132] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0133] The base layer graphene slurry is coated on one side of the carbon fiber layer preform, and the coating amount is 0.013g / cm 2 , and then put the composite material into a common oven and dry it at 120℃ for 6h. The composite material was completely peeled off from the glass plate and then transferred to a roller press. The rolling temperature was 80℃ and the rolling spacing was 100μm. The rolling was repeated twice. The base layer graphene slurry was sprayed on the other side of the composite material with a spraying amount of 0.013g / cm 2 , drying, repeating the above rolling operation twice. Then put it into a high temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, the gas atmosphere is nitrogen. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​70cm×70cm.

[0134] (5) Preparation of microporous graphene slurry:

[0135] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 600mg of the above heat-treated graphene powder, 600mg of carbon black (CabotVulcan XC-72R, average particle size 50nm), and 600mg of polyvinylidene fluoride (mass ratio of 1:1:1), mix the three evenly, and grind them in a mortar for 30min. Then disperse them in 16g of N-methylpyrrolidone by ultrasonication to form a viscous and flowable microporous layer slurry.

[0136] (6) Composite of base layer and microporous layer:

[0137] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0138] Example 5

[0139] (1) Carbon fiber filaments on glass substrate:

[0140] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0141] (2) Preparation of carbon fiber layer preform:

[0142] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0143] (3) Preparation of graphene slurry for the base layer:

[0144] 3.88 g of waterborne polyurethane (solid content 60%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred. Then, 3.88 g of epoxy resin A glue and 1.94 g of epoxy resin B glue (Fossil) were added in sequence, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0145] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0146] The carbon fiber preform was soaked in the above-mentioned base layer graphene slurry for 6 hours, then taken out and placed in a common oven and dried at 120°C for 6 hours. The composite material was completely peeled off from the glass plate, and then placed in a high-temperature furnace and heated to 1000°C at a rate of 5°C / min, and then carbonized for 30 minutes in a nitrogen atmosphere. Naturally cooled to room temperature and taken out to obtain a gas diffusion layer base layer (carbon fiber-graphene-polymer composite base layer) with an area of ​​40cm×40cm, a thickness of 0.125mm, and a conductivity of 9.70S / mm.

[0147] (5) Preparation of microporous graphene slurry:

[0148] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 600mg of the above heat-treated graphene powder, 600mg of carbon black (KB EC-600JD, average particle size 34nm), and 600mg of polyvinylidene fluoride (mass ratio of 1:1:1), mix the three evenly, and grind them in a mortar for 30min. Then disperse them in 16g of N-methylpyrrolidone by ultrasonication to form a viscous and flowable microporous layer slurry.

[0149] (6) Composite of base layer and microporous layer:

[0150] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0151] Example 6

[0152] (1) Carbon fiber filaments on glass substrate:

[0153] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0154] (2) Preparation of carbon fiber layer preform:

[0155] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0156] (3) Preparation of graphene slurry for the base layer:

[0157] 3.88 g of waterborne polyurethane (solid content 60%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred. Then, 3.88 g of epoxy resin A glue and 1.94 g of epoxy resin B glue (Fossil) were added in sequence, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0158] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0159] The base layer graphene slurry is scraped onto one side of the carbon fiber layer preform with a scraper, and the coating amount is 0.013g / cm 2 , and then put the composite material into a common oven and dry it at 120℃ for 6h. The composite material was completely peeled off from the glass plate and then transferred to a roller press. The rolling temperature was 80℃ and the rolling spacing was 100μm. The rolling was repeated twice. The base layer graphene slurry was sprayed on the other side of the composite material with a spraying amount of 0.013g / cm 2 , drying, repeating the above rolling operation twice. Then put it into a high temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, the gas atmosphere is nitrogen. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​40cm×40cm.

[0160] (5) Preparation of microporous graphene slurry:

[0161] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 800mg of the above heat-treated graphene powder, 800mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 200mg of polyvinylidene fluoride (mass ratio of 4:4:1), mix the three evenly, and grind them in a mortar for 30min. Then ultrasonically disperse them in 16g of N-methylpyrrolidone to form a viscous and flowable microporous layer slurry.

[0162] (6) Composite of base layer and microporous layer:

[0163] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0164] Example 7

[0165] (1) Carbon fiber filaments on glass substrate:

[0166] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0167] (2) Preparation of carbon fiber layer preform:

[0168] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0169] (3) Preparation of graphene slurry for the base layer:

[0170] 35 kg of artificial graphite powder, 2.5 kg of sodium carboxymethyl cellulose (CMC) and 200 kg of deionized water were mixed and mechanically exfoliated using a nano-grinding machine to prepare a graphene slurry.

[0171] Take 26.5g of the above-mentioned graphene slurry (aqueous system, solid content 13.58%) and mix with 225mg of polyacrylic acid (McLean, molecular weight 450000) and 7mg of polyvinyl alcohol (McLean, molecular weight 1750) to obtain a base layer graphene slurry, and make the carboxyl group in the polyacrylic acid react with the hydroxyl group in the polyvinyl alcohol and the graphene slurry CMC in a 1:1 ratio.

[0172] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0173] The base layer graphene slurry is sprayed on one side of the carbon fiber layer preform with a spray gun, and the spraying amount is 0.008g / cm 2 , and then put the composite material into a common oven, and then transfer it to a roller press, with a rolling temperature of 80°C and a rolling spacing of 100μm, and repeat the rolling for 3 times. Dry at 120°C for 6h. Remove the composite material completely from the glass plate, and spray the base layer graphene slurry on the other side of the composite material, with a spraying amount of 0.008g / cm 2 , drying, repeating the above rolling operation twice. Then put it into a high temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, the gas atmosphere is nitrogen. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​40cm×40cm, a thickness of 0.111mm, and a conductivity of 10.16S / mm.

[0174] (5) Preparation of microporous graphene slurry:

[0175] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 800mg of the above heat-treated graphene powder, 800mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 400mg of polyvinylidene fluoride (mass ratio of 2:2:1), mix the three evenly, and grind them in a mortar for 30min. Then disperse them in 16g of N-methylpyrrolidone by ultrasonication to form a viscous and flowable microporous layer slurry.

[0176] (6) Composite of base layer and microporous layer:

[0177] The above-mentioned microporous layer slurry was coated on one side of the base layer (3cm×3cm) with a coating amount of 6mg / cm2, placed in a muffle furnace (air atmosphere, 350℃), kept warm for 30min, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0178] Example 8

[0179] (1) Carbon fiber filaments on glass substrate:

[0180] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0181] (2) Preparation of carbon fiber layer preform:

[0182] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0183] (3) Preparation of graphene slurry for the base layer:

[0184] 36.21 g of waterborne polyurethane (solid content 60%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0185] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0186] The base layer graphene slurry is coated on one side of the carbon fiber layer preform, and the coating amount is 0.013g / cm 2 The composite material was then placed in a common oven and dried at 120°C for 6 hours. The composite material was completely removed from the glass plate, and the base layer graphene slurry was sprayed on the other side of the composite material with a coating amount of 0.013 g / cm 2 , drying. Then place the composite material on a flat hot press for hot pressing, set the hot pressing temperature to 270℃, the pressure to 320KPa, and the holding time to 20min. Then put it in a high-temperature furnace and heat it to 1000℃ at a rate of 5℃ / min, and then carbonize it for 30min, with a nitrogen atmosphere. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer substrate (carbon fiber-graphene-polymer composite substrate) with an area of ​​40cm×40cm.

[0187] (5) Preparation of microporous graphene slurry:

[0188] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 800mg of the above heat-treated graphene powder, 800mg of carbon black (Carbon black acetylene, average particle size 42nm), and 100mg of polytetrafluoroethylene (mass ratio of 8:8:1), mix the three evenly, and grind them in a mortar for 30min. Then ultrasonically disperse them in 16g of N-methylpyrrolidone to form a viscous and flowable microporous layer slurry.

[0189] (6) Composite of base layer and microporous layer:

[0190] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0191] Example 9

[0192] (1) Carbon fiber filaments on glass substrate:

[0193] The carbon fiber is spread in a large water tank with a length, width, depth and placement height of 1.8m, 0.6m, 0.015m and 0.75m respectively, and the bottom is smooth tempered glass. The carbon fiber roll is placed at one end of the large water tank and flush with the height of the large water tank. The carbon fiber bundle is introduced from the carbon fiber roll into the large water tank filled with ultrapure water through a guide roller and the carbon fiber bundle is pulled to the other end of the large water tank without flipping. The carbon fiber bundle is left to stand in ultrapure water for 30 minutes, and the carbon fiber is spread to the horizontal width of the water tank, pulled longitudinally, and spread horizontally at the same time. After repeated multiple times, a uniformly spread carbon fiber filament with a width of 40cm is obtained.

[0194] (2) Preparation of carbon fiber layer preform:

[0195] The uniformly spread carbon fiber filaments are wound on a smooth tempered glass plate with a length and width of 0.4 m and 0.4 m respectively, and the filaments are simultaneously spread during the winding process. Eight layers of carbon fiber (four layers each in the horizontal and vertical directions) are alternately wound on the surface of the smooth tempered glass plate to obtain a carbon fiber layer preform.

[0196] (3) Preparation of graphene slurry for the base layer:

[0197] 18.11 g of water-soluble phenolic resin (solid content 70%, McLean) was added to 40 g of homemade graphene slurry (water system, solid content 13.58%) mechanically peeled off by a sand mill in the laboratory, and the mixture was mixed and stirred to obtain a base layer graphene slurry.

[0198] (4) Preparation of carbon fiber-graphene-polymer composite substrate layer:

[0199] The base layer graphene slurry is coated on one side of the carbon fiber layer preform, and the coating amount is 0.013g / cm 2 The composite material was then placed in a common oven and dried at 120°C for 6 hours. The composite material was completely removed from the glass plate, and the base layer graphene slurry was sprayed on the other side of the composite material with a coating amount of 0.013 g / cm 2 , dried. The composite material is then placed on a flat hot press for hot pressing, with the hot pressing temperature set to 270°C, the pressure set to 320KPa, and the holding time set to 20min. After testing, the conductivity of the base layer is 3.71S / mm. Then put it in a high-temperature furnace and heat it to 1000°C at a rate of 5°C / min, and then carbonize it for 30min in a nitrogen atmosphere. Naturally cool it to room temperature and take it out to obtain a gas diffusion layer base layer (carbon fiber-graphene-polymer composite base layer) with an area of ​​40cm×40cm and a thickness of 0.128mm. After testing, the conductivity of the base layer after high-temperature carbonization is 10.81S / mm, and the conductivity is greatly improved.

[0200] (5) Preparation of microporous graphene slurry:

[0201] Take graphene powder (laboratory sand mill mechanical exfoliation, freeze drying, particle size of 50μm) and place it in a tube furnace air atmosphere at 450℃, keep it warm for 2h to remove organic matter, then place it in a hydrogen argon atmosphere at 800℃ and keep it warm for 30min to completely remove the functional groups. Take 800mg of the above heat-treated graphene powder, 600mg of carbon black (Carbonblack acetylene, average particle size 42nm), and 600mg of polyvinylidene fluoride (mass ratio of 4:3:3), mix the three evenly, and grind them in a mortar for 30min. Then ultrasonically disperse them in 16g of N-methylpyrrolidone to form a viscous and flowable microporous layer slurry.

[0202] (6) Composite of base layer and microporous layer:

[0203] The microporous layer slurry was coated on one side of the base layer (3 cm × 3 cm) at a coating amount of 6 mg / cm 2 , placed in a muffle furnace (air atmosphere, 350°C), kept warm for 30 minutes, and dried to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

[0204] Figure 3 This is a graph showing the tensile strength test results of the base layer prepared in step (4) of this embodiment before and after carbonization. Figure 3 The a line in the figure is the tensile strength of the substrate before carbonization. Figure 3 b in the figure is the tensile strength of the base layer after carbonization. It can be seen from the figure that the tensile strength of the base layer after carbonization can reach 20MPa.

[0205] The pore size distribution of the base layer in the gas diffusion layer of carbon fiber filaments, graphene and polymer composites prepared in Example 3 and Example 8 was measured by mercury intrusion porosimetry. The test results are as follows: Figure 4 As shown, it can be seen from the figure that the pore size distribution of the base layer is uniform.

[0206] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer, characterized in that: The following steps are involved: 1) Spreading the carbon fiber bundle to obtain spread carbon fiber filaments, and then winding the spread carbon fiber filaments alternately vertically and horizontally on a base material with a smooth surface to obtain a carbon fiber layer preform; Mixing graphene slurry with polymer material to prepare base layer graphene slurry; Dispersing carbon black, graphene powder and a hydrophobic binder in a solvent to obtain a microporous layer slurry; 2) coating the base layer graphene slurry on both sides of the carbon fiber layer preform, drying, hot rolling or hot holding, and then high-temperature carbonizing in an inert gas to obtain the base layer; 3) coating the microporous layer slurry on one side of the substrate layer, and drying the slurry to obtain a gas diffusion layer composited with carbon fiber filaments, graphene and polymer.

2. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 1, characterized in that: The width of the unfolded carbon fiber filaments described in step 1) is 40 to 70 cm; The length of the base material is 0.3 to 0.8 m, and the width of the base material is 0.3 to 0.8 m; The number of winding layers is 6 to 10 layers.

3. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 2, characterized in that: The mass ratio of the graphene slurry to the polymer material in step 1) is 1 to 120:1; The solid content of the graphene slurry is 13.5-17.5%; The number of atomic layers of graphene in the graphene slurry is less than 10, and the length and width of a single microsheet of graphene are independently between 2 and 7 mm.

4. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 3, characterized in that: The polymer material in step 1) includes one or more of waterborne polyurethane, epoxy resin AB glue, water-soluble phenolic resin, polyacrylic acid and polyvinyl alcohol; The solid content of the polymer material is ≥60%.

5. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to any one of claims 1 to 4, characterized in that: The mass ratio of carbon black, graphene powder, hydrophobic binder and solvent in step 1) is 8:8:1-8:160-200; The carbon black has a particle size of 30 to 50 nm and a specific surface area of ​​200 to 1400 m 2 / g; The hydrophobic binder is polytetrafluoroethylene and / or polyvinylidene fluoride, and the viscosity of the hydrophobic binder is 0.2 to 20 Pa·S; The solvent includes one or more of N-methylpyrrolidone, ethanol and water.

6. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 5, characterized in that: The mass ratio of the total coating amount of the base layer graphene slurry to the carbon fiber layer preform in step 2) is 2 to 5:1; The drying temperature is 80-120°C and the drying time is 4-8h; The temperature of the hot roller pressing is 70-90°C, the roller pressing interval is 0.06-0.12mm, and the number of hot roller pressing is 2-5 times; The temperature of the heat-pressing is 250-270° C., the pressure of the heat-pressing is 220-420 KPa, and the time of the heat-pressing is 20-30 minutes.

7. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 6, characterized in that: The temperature of the high temperature carbonization in step 2) is 1000-1200° C., the time is 30-60 min, and the heating rate is 5-15° C. / min.

8. The method for preparing a gas diffusion layer composited with carbon fiber filaments, graphene and polymer according to claim 7, characterized in that: The coating amount of the microporous layer slurry on the surface of the base layer in step 3) is 1-8 mg / cm 2 ; The drying temperature is 300-400° C. and the drying time is 30-60 minutes.

9. The method for preparing a carbon fiber filament, graphene and polymer composite gas diffusion layer according to any one of claims 1 to 8, wherein the carbon fiber filament, graphene and polymer composite gas diffusion layer is prepared, characterized in that: The carbon fiber filaments, graphene and polymer composite gas diffusion layer comprises a base layer and a microporous layer; The thickness of the base layer is 0 to 130 μm, the thickness of the base layer is not 0, and the bending strength is ≥ 10 MPa; The thickness of the microporous layer is 10-40 μm.

10. Use of the carbon fiber filaments, graphene and polymer composite gas diffusion layer according to claim 9 in a fuel cell.